Rap1 regulates TIP60 function during fate transition between two-cell-like and pluripotent states - Barry, Raymond Mario; Sacco, Olivia; Mameri, Amel; Stojaspal, Martin; Kartsonis, William; Shah, Pooja; De Ioannes, Pablo; Hofr, Ctirad; Côté, Jacques; Sfeir, Agnel (Genes & development, 2022)
In mammals, the conserved telomere binding protein Rap1 serves a diverse set of nontelomeric functions, including activation of the NF-kB signaling pathway, maintenance of metabolic function in vivo, and transcriptional regulation. Here, we uncover the mechanism by which Rap1 modulates gene expression. Using a separation-of-function allele, we show that Rap1 transcriptional regulation is largely independent of TRF2-mediated binding to telomeres and does not involve direct binding to genomic loci. Instead, Rap1 interacts with the TIP60/p400 complex and modulates its histone acetyltransferase activity. Notably, we show that deletion of Rap1 in mouse embryonic stem cells increases the fraction of two-cell-like cells. Specifically, Rap1 enhances the repressive activity of Tip60/p400 across a subset of two-cell-stage genes, including Zscan4 and the endogenous retrovirus MERVL. Preferential up-regulation of genes proximal to MERVL elements in Rap1-deficient settings implicates these endogenous retroviral elements in the derepression of proximal genes. Altogether, our study reveals an unprecedented link between Rap1 and the TIP60/p400 complex in the regulation of pluripotency.
Keywords: Animals; telomery; Mammals; Telomere-Binding Proteins; regulace genové exprese; Gene Expression Regulation; zvířata; Telomere; Mice; savci; proteiny vázající telomery; Mouse Embryonic Stem Cells; genom; myší embryonální kmenové buňky; Genome; myši